Preoperative Pain Catastrophizing Is Associated with Early Postoperative Pain and Suboptimal Early Weight Loss after Sleeve Gastrectomy - ANGIN Y. S.; Özsoy Z.; Yıldırım M.; Daşıran M. F.; DALDAL E.; SÜREN M.; Okan İ.; BÜLBÜLOĞLU E.; Şahin M. (My University, 2026)
Objective: To evaluate whether preoperative Pain Catastrophizing Scale (PCS) scores predict postoperative pain, opioid use, and suboptimal early weight loss after sleeve gastrectomy. Methods: In this prospective single-center cohort, 80 adults undergoing laparoscopic sleeve gastrectomy completed PCS, Beck Depression, and Beck Anxiety inventories preoperatively. Pain was recorded using the Numeric Rating Scale (NRS) at several time points in the first 24 h; opioid consumption was converted to morphine equivalents. Weight loss was assessed at 6 months as percent excess weight loss (%EWL). Receiver-operating characteristic (ROC) analysis was performed to determine the optimal PCS threshold for identifying patients at risk of suboptimal early weight loss (%EWL < 60) at 6 months. Multivariable logistic regression analysis was performed adjusting for age, sex, body mass index (BMI), depression, and anxiety. Results: Higher PCS scores strongly correlated with NRS pain at all time points (Spearman correlation coefficient [r] ≥ 0.70 at 2 h and 8 h; p < 0.001) and greater opioid use. ROC analysis identified PCS of ≥26 as the optimal cut-off for predicting %EWL of <60 (p = 0.048). Patients with PCS of ≥26 achieved lower mean %EWL (69.7 ± 19.5%) than those with PCS < 26 (77.7 ± 15.0%). In multivariable logistic regression analysis, PCS of ≥26 was associated with increased odds of suboptimal early weight loss (OR = 3.27, 95% CI: 0.51–21.10); however, this association did not reach statistical significance after adjustment. Conclusion: High PCS scores identify patients at risk for severe early pain and suboptimal early weight loss trajectory. Routine PCS screening may guide targeted perioperative pain management and behavioral interventions to improve bariatric outcomes.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Hemşirelik; Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Nursing; Nutrition and Dietetics; Agricultural Sciences; Agriculture; Health Sciences; Tarım ve Çevre Bilimleri (Age); Klinik Tıp (Med); Tarım Bilimleri; Klinik Tıp; Beslenme ve Diyetetik; Cerrahi; Agriculture & Environment Sciences (Age); Clinical Medicine (Med); Clinical Medicine; Nutrition & Dietetics; Surgery; Tıbbi ve Cerrahi Hemşirelik; Medical and Surgical Nursing; bariatric surgery; catastrophizing; pain management; psychosocial factors; sleeve gastrectomy; weight loss